Éducation inclusive : initiative de formation menée au Canada et interrogations sur les difficultés encourues en cherchant à soutenir la « voix » de l’élève - Diane Farmer; Christine Connelly; Miriam Greenblatt (Recherches en Éducation)
This text stems from a training initiative on inclusive education carried out with teachers in two French-language schools in Toronto. Inclusive education is a movement that aims to imple-ment teaching practices that are sensitive to students’ culture and to resist all forms of discrimination. Even though the principles of inclusive education have been formalized in ministry policy, there remain numerous issues related to putting them into prac-tice in everyday classroom life. In the spirit of accompanying school staff, we facilitated an initiative in which teachers developed various classroom projects over a period of one school year. In the first part of our paper, we will present the training model we developed and in the second part, we seek to delve deeper into an issue raised by a team of teachers: how to support student voice in an inclusive education process. We will also examine the contentious notion of children's or students’ voice, an area of intervention targeted by inclusive educa-tion. In this initiative we ask: how can discrimination be addressed without reducing groups experiencing discrimination to the status of victims? How to support the voice of students in an inclusive education process? These major questions will guide the overall reflection proposed here.